4\x-2 - 15\x=2
4x- 15(x-2)\x(x-2)=2
4x - 15x - 30\ x^2 - 2x= 2
-11x-30\x^2 - 2x - 2=0
-7x+30 - 2x^2\x(x-2)=0
-7x +30 - 2x^2=0 \ -1
2x^2 +7x -30=0
D= 7^2 -4*2*-30=289=17
x1=-7 - 17\2*2= -24\4=-6
x2= -7 + 17\2*2 = 10\4=5\2=2,5
ответ: -6и 2,5
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
4\x-2 - 15\x=2
4x- 15(x-2)\x(x-2)=2
4x - 15x - 30\ x^2 - 2x= 2
-11x-30\x^2 - 2x - 2=0
-7x+30 - 2x^2\x(x-2)=0
-7x +30 - 2x^2=0 \ -1
2x^2 +7x -30=0
D= 7^2 -4*2*-30=289=17
x1=-7 - 17\2*2= -24\4=-6
x2= -7 + 17\2*2 = 10\4=5\2=2,5
ответ: -6и 2,5